Interplant Communication of Tomato Plants through Underground Common Mycorrhizal Networks - Song, Yuan Yuan; Zeng, Ren Sen; Xu, Jian Feng; Li, Jun; Shen, Xiang; Yihdego, Woldemariam Gebrehiwot (PLOS ONE, 2010)
Plants can defend themselves to pathogen and herbivore attack by responding to chemical signals that are emitted by attacked plants. It is well established that such signals can be transferred through the air. In theory, plants can also communicate with each other through underground common mycorrhizal networks (CMNs) that interconnect roots of multiple plants. However, until now research focused on plant-to-plant carbon nutrient movement and there is no evidence that defense signals can be exchanged through such mycorrhizal hyphal networks. Here, we show that CMNs mediate plant-plant communication between healthy plants and pathogen-infected tomato plants (Lycopersicon esculentum Mill.). After establishment of CMNs with the arbuscular mycorrhizal fungus Glomus mosseae between tomato plants, inoculation of ‘donor’ plants with the pathogen Alternaria solani led to increases in disease resistance and activities of the putative defensive enzymes, peroxidase, polyphenol oxidase, chitinase, β-1,3-glucanase, phenylalanine ammonia-lyase and lipoxygenase in healthy neighbouring ‘receiver’ plants. The uninfected ‘receiver’ plants also activated six defence-related genes when CMNs connected ‘donor’ plants challenged with A. solani. This finding indicates that CMNs may function as a plant-plant underground communication conduit whereby disease resistance and induced defence signals can be transferred between the healthy and pathogen-infected neighbouring plants, suggesting that plants can ‘eavesdrop’ on defence signals from the pathogen-challenged neighbours through CMNs to activate defences before being attacked themselves.